Winter soil temperature varies with canopy cover in Siberian larch forests - Michael M Loranty; Heather D Alexander; Sergey P Davydov; Alexander L Kholodov; Heather Kropp; Michelle C Mack; Susan M Natali; Nikita S Zimov (Environmental Research Letters, 2024)
In the Arctic, winter soil temperatures exert strong control over mean annual soil temperature and winter CO _2 emissions. In tundra ecosystems there is evidence that plant canopy influences on snow accumulation alter winter soil temperatures. By comparison, there has been relatively little research examining the impacts of heterogeneity in boreal forest cover on soil temperatures. Using seven years of data from six sites in northeastern Siberia that vary in stem density we show that snow-depth and forest canopy cover exert equally strong control on cumulative soil freezing degrees days (FDD _soil ). Together snow depth and canopy cover explain approximately 75% of the variance in linear models of FDD _soil and freezing n -factors ( n _f ; calculated as the quotient of FDD _soil and FDD _air ), across sites and years. Including variables related to air temperature, or antecedent soil temperatures does not substantially improve models. The observed increase in FDD _soil with canopy cover suggests that canopy interception of snow or thermal conduction through trees may be important for winter soil temperature dynamics in forested ecosystems underlain by continuous permafrost. Our results imply that changes in Siberian larch forest cover that arise from climate warming or fire regime changes may have important impacts on winter soil temperature dynamics.